2021
DOI: 10.1002/tsm2.276
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of runners meeting acute kidney injury criteria following a 161‐km ultramarathon

Abstract: The incidence of acute kidney injury (AKI) associated with ultramarathon running is varied partially because onsite measurement of serum creatinine concentration (Cr) is rarely performed at races due to logistical challenges. We conducted a prospective observational study using blood samples from volunteer athletes before and immediately after the Leadville Trail 100 Run in August 2014. The goals of our study were to determine the incidence of those meeting the AKI criteria immediately following the ultramarat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…These selected articles were fully reviewed and evaluated to verify whether they met the inclusion criteria. A total of 28 articles were accepted for final review, 13 of which focused on AKI ( Table 1 ) [ 28 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and the remaining 15 on EAH ( Table 2 ) [ 24 , 27 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Nine of the studies reported combined results of AKI and EAH [ 24 , 27 , 28 , 44 , 45 , 49 , 51 , 52 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These selected articles were fully reviewed and evaluated to verify whether they met the inclusion criteria. A total of 28 articles were accepted for final review, 13 of which focused on AKI ( Table 1 ) [ 28 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and the remaining 15 on EAH ( Table 2 ) [ 24 , 27 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Nine of the studies reported combined results of AKI and EAH [ 24 , 27 , 28 , 44 , 45 , 49 , 51 , 52 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The one-stage category included races ranging from 45 to 217 km. Single-stage races were classified into three different groups according to length [ 5 ]: 14 extra-long races (≥100 km) [ 24 , 44 , 47 , 50 , 51 , 52 , 53 , 54 , 57 , 58 , 59 , 62 , 64 , 66 , 67 ], 3 long ones (70–99 km) [ 27 , 28 , 45 ] and 8 medium ones (>42.195–69 km) [ 44 , 47 , 49 , 54 , 55 , 60 , 64 , 65 ]. The cumulative elevation gains and losses ranged between 645 m [ 59 ] and 12,000 m [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, several studies have focused on studying acute kidney injury (AKI) after performing a physically demanding exercise ( Lipman et al, 2014 ; Traiperm et al, 2016 ; Mansour et al, 2017 ; González et al, 2019 ; Rojas-Valverde et al, 2019 ; Poussel et al, 2020 ; Khodaee et al, 2021 ). Contrary to other acute pathological alterations, renal function has been shown to be normalized 24 h after running a long-distance race.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to other acute pathological alterations, renal function has been shown to be normalized 24 h after running a long-distance race. As a result, the collection of biomarkers related to AKI have been usually restricted to the running phase ( Lipman et al, 2014 ; Belli et al, 2018 ) or to the first 24 h of the recovery phase ( McCullough et al, 2011 ; Traiperm et al, 2016 ; Mansour et al, 2017 ; Khodaee et al, 2021 ). However, we observed that glomerular filtration rate (GFR) significantly worsened 48 h after marathon running ( González et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%